Design of Waveguide Integrated Ge-Quantum-Well Electro-Absorption Modulators - Zhao, Hong-Wei (红卫 赵); Hu, Wei-Xuan (讳玄 胡); Xue, Chun-Lai (春来 薛); Cheng, Bu-Wen (步文 成); Wang, Qi-Ming (启明 王) (Chinese physics letters, 2011)
We present two designs for a waveguide Oe-quantum-well electro-absorption modulator. In our designs, the strip SOI waveguides are butt-coupled and evanescent-coupled to the modulator, respectively. The proposed Gequantum-weB electro-absorption modulator is based on quantum-confined Stark effect （QCSE）, having a 3-dB bandwidth above 50GHz, as well as a low switching power （around 60fJ/bit at 1435nm）. In the butt-coupled design, the optimized extinction ratio is up to 11.4 dB, while the insertion loss is only 6. 74 dB. For the second one, which utilizes evanescent coupling, the extinction ratio and insertion loss are 9.18 dB and 6. 72 dB, respectively.